Hubungan Penggunaan Gedget Dan Media Sosial Dengan Minat Belajar Mahasiswa Universitas Imelda Medan Kota Medan Tahun 2020 - Eva Nirwana Hutabarat (Pusdikra Publishing, 2020)
The purpose of this study was to determine how much the relationship of use of Gedget and social media with interest in learning female students. This type of research is an analytical survey with a cross sectional approach. The research was conducted at the D-III D-III Prodi of the Imelda University. The population of the study of all semester III students was 70 people, and were all sampled. Data were analyzed in univariate and bivariat using the Chi-Square test. The results showed that the use of Gedget and Social Media Student D-III D-III Midwifery University of Imelda in the Enough category (50.0%). Interest in learning college students in the good category (50.0%). There is a significant relationship between the relationship between the use of Gedget and social media with interest in learning Student D-III D-III Study Program Imelda, with a significant value (P) = 0.000 <0.05.